PV control systems using iterated local search MPPT with an improved switched capacitor DC-DC converter. (30th April 2020) - Kumar, J.K. Mohan; Rauf, H. Abdul; Umamaheswari, R.
An optimisation to the steady state performance of wide range of switched capacitor (SC) converters made use in control of photo voltaic (PV) systems that aims to enhance its efficiency and output regulation performed by a switched capacitor direct current (SCDC) converter is proposed. This uses many power converters to effectively transmit power via a large cable with greater electro-magnetic interference (EMI). Under no-load conditions, this explained model shows that an ideal DC voltage transformation is achieved by the converter and the loss during the conversion are altered because the drop in voltage due to the non-zero load current measured at the impedance at load side has lesser electro-magnetic interference (EMI). The charging of capacitor and loss during discharging and the conduction loss at resistance is mainly due to the impedance of output resistance. Followed by this, our DC to DC converter is extended to a smart control technique to track maximum power point (MPP) of a PV system with constraints of varying temperature and irradiance along with iterated local search (ILS).